Hepatic gateways. (3rd May 2016) - Udupa, K. Venkatesha; Brayden, David J.; Winter, Desmond C.; Baird, Alan W.
ABSTRACT: The intestinal mucosal barrier contributes to homeostasis by limiting systemic dissemination of microbes and toxins while allowing nutrients to pass through to the systemic circulation. In a recent issue of Science, Spadoni et al . demonstrated a novel mechanism to enable this selectivity: the existence of a gut-vascular barrier (GVB) as indicated by a series of studies on the interaction between murine and human intestine with Salmonella typhimurium species . They showed that (i) enteroglial cells and pericytes in contact with endothelial cells (ECs) form the GVB (ii) Salmonella typhimurium can penetrate it by a mechanism dependent on the pathogenicity island (Spi) 2–encoded type III secretion system and on decreased β-catenin dependent signaling in gut endothelial cells. Understanding the GVB may provide new insights into the regulation of the gut-liver axis.